Non-equilibrium plasma properties of electric arc discharge in air between copper electrodes - Boretskij, V.; Veklich, A.; Cressault, Y.; Gleizes, A.; Teulet, Ph. (Вопросы атомной науки и техники, 2012)
Spectroscopy investigations of plasma of free burning electric arc discharge as well as discharge in air flow of 6.45 slpm at currents 3.5, 30, 50 and 100 A were carried out. Plasma state deviation from thermodynamic equilibrium was found at arc current 100 A. Two-temperatures model was used to estimate plasma composition at arc current 100 A.